Revisiting darwinian teleology: A case for inclusive fitness as design explanation. (August 2019) - Huneman, Philippe
Abstract: This paper elaborates a general framework to make sense of teleological explanations in Darwinian evolutionary biology. It relies on an attempt to tie natural selection to a sense of optimization. First, after assessing the objections made by any attempt to view selection as a maximising process within population genetics, it understands Grafen's Formal Darwinism (FD) as a conceptual link established between population genetics and behavioral ecology's adaptationist framework (without any empirical commitments). Thus I suggest that this provides a way to make sense of teleological explanations in biology under their various modes. Then the paper criticizes two major ways of accounting for teleology: a Darwinian one, the etiological view of biological functions, and a non-Darwinian one, here labeled "intrinsic teleology" view, which covers several subtypes of accounts, including plasticity-oriented conceptions of evolution or organizational views of function. The former is centered on traits while the latter is centered on organisms; this is shown to imply that both accounts are unable to provide a systematic understanding of biological teleology. Finally the paper argues that viewing teleology as maximization of inclusive fitness along the FD lines as understood here allows one to make sense of both the design of organisms and the individual traits as adaptions. Such notion is thereby claimed to be the proper meaning of teleology in evolutionary biology, since it avoids the opposed pitfalls of etiological views and intrinsic-teleology view, while accounting for the same features as they do. Highlights: Presents an account of Darwinian teleology based on inclusive fitness (IF Teleology), through Formal Darwinism as a bridge between behavioral ecology's and population genetics' uses of the concept of natural selection. Criticizes dominant accounts of biological teleology i.e. etiological theory of functions, and 'intrinsic-teleology' accounts based on the purposive character of organisms (e.g. plasticity-centered accounts of evolution, organizational accounts of functions, etc.) Argues that IF teleology recognizes both the teleology of traits or parts, and the teleology of organisms themselves, thus supersedes the two rival views of biological teleology. Argues that IF teleology explains the dual designed character of organisms, namely having been designed and having a design.